The Government Responsibility for Oil and Gas Management Based on Constitution of Indonesia - Ardiansah, Ardiansah; Asnawi, Eddy; Fahmi, Sudi; Ismail, Syaimak (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
On September 3, 2022, fuel prices were raised by President Joko Widodo, with advocates arguing that the increase is necessary to safeguard the State Revenue and Expenditure Budget. Dissenting groups contended the hike was inappropriate, citing a dissonance between the identified problem and the proposed solution. Therefore, this study aims to analyze the legal aspects, policies and the role of the government in ensuring the welfare of Indonesian citizens through oil and gas management. Using a normative legal study methodology, the study used both statutory and analytical methods. The results showed a discrepancy between the increase in fuel price and the principles outlined in Article 33 and the Preamble of the 1945 Constitution of the Republic of Indonesia. The government, as the representative of the state, holds the authority to manage the mining sector's economy, aiming to maximize prosperity for citizens. Adhering to the ideology of a welfare state, the responsibility to provide basic social needs and foster prosperity is assigned to the government.